Islamic Education's Alternative Approach to Nurturing Mental Health and Psychological Well-being - Ikhwan, M.; Walidin, Warul; Mahmud, Salami (International Journal of Education, Language, and Social Science, 2023)
This article explores the significance of addressing mental health from an Islamic standpoint as a means to attain psychological well-being. In Islam, maintaining mental health is advocated through fostering a connection with Allah SWT, attaining life balance, seeking support from others, practicing Islamic values in daily life, and refraining from factors that may impact mental well-being. The article delves into the positive correlation between good mental health and enhanced happiness and productivity in one's daily life. Employing qualitative research methods with a narrative approach, data is gathered from diverse sources such as books, journals, and credible references. The collected data is subsequently analyzed and interpreted to fulfill the research objectives, shedding light on how focusing on mental health aspects can enhance an individual's quality of life and foster psychological well-being. Consequently, this article presents an overview of Islamic approaches to addressing mental health as an alternative pathway to achieving psychological well-being. By nurturing a relationship with Allah SWT, maintaining life balance, seeking social support, integrating Islamic values into daily life, and avoiding detrimental influences, individuals can effectively care for their mental health. This holistic framework, encompassing both spiritual and social dimensions, reflects the realization of Islamic teachings in promoting mental well-being.